Analisis Pembangunan Ekonomi Daerah Dalam Perspektif Potensi Sumber Daya: Studi Kasus Kabupaten Lebong Sebagai Kabupaten Konservasi - Sunoto Sunoto; Bertha Iin Esti Indraswanti (Convergence: The Journal of Economic Development, 2021)
The purpose of this research was to analyze economic development of Lebong Regency in potential resources perspective. Base on BPS secondary time series data (2017-2020), descriftive analysis was used to analyze economic development, include DLQ and SS analysis. Lebong did not depend on premier sector to growth. As a conservation region, potential resources can be explored to increase value added. Even, the labor force had low education. Leading sectors in employment absortion are sectors which unskill labor. The higher output productivity performs by secunder and tertier sectors. Lebong have carbon conservation programme, and develop tourism base on environment. Keywords:   Economic Development, Conservation Region.